Central bank independence and its relationship to inflation - Helder Ferreira de Mendonça (CEPAL Review, 2005)
This paper builds on earlier studies of central bank independence (CBI), making a comparison of the rankings of central banks for 15 countries through three different indices. The analysis reveals that there is no shared concept of CBI and that the indices are a measure of the inflation bias. The Brazilian case is used as an example, with the objective of examining the impact on inflation of an increase in independence over time, as measured by Cukierman’s index. The findings indicate that CBI is a consequence of the conduct of monetary policy and that it is not an adequate framework for developing credibility.